Return to training and competition after COVID-19 in professional football - Casais-Martinez, L.; Sanroman-Cortes, Z.; Del Hoyo-Lora, M.; Solla-Aguiar, J.; Lago-Penas, C. (Sport Performance & Science Reports, 2020)
If the COVID-19 pandemic situation improves quickly andgovernance permit to restart sports events, an appropriatesport-specific conditioning should be granted considering three key points: (i) the effects of possible asymmetrical detraining leading to modification of ligament, muscle and tendonproperties; (ii) training load after inactivity periods and (iii) density of matches, which will necessarily be increased afterbreak period to be able to finish the football competitions. This manuscript provides specific recommendations to the resumption of training.